Interval type-2 fuzzy logic control optimize by spiral dynamic algorithm for two-wheeled wheelchair - Nurul Fadzlina, Jamin (2020)
The reconfiguration of the two-wheeled wheelchair system with movable payload has been investigated within the current study towards permitting multi-task operations; through enhanced maneuverability on a flat surface under the circumstances of disturbance rejections during forward and backward motions, as well as motions on the inclined surface for uphill and downhill motions; while having height extensions of the wheelchair’s seat. The research study embarks on three objectives includes developing Interval Type-2 Fuzzy Logic Control (IT2FLC) as the control system, design a Spiral Dynamic Algorithm (SDA) for IT2FLC in stabilizing the designed double-link twowheeled wheelchair system, and optimize the input-output gains and control parameters. The two-wheeled system gives lots of benefits to the user such as less space needed to turn the wheelchair, able to move in the narrow spaces, having eye-to-eye contact with normal people, and can reach stuff on the higher shelve. However, the stability of the twowheeled system will produce high fluctuations due to the uncertainties while stabilizing the system in the upright position. Indirectly, it also caused the long travelled distance and high magnitude of tilt angle and torque. Thus, IT2FLC has been proposed as the compatible control strategy for disturbance rejections to overcome uncertainties for enhanced system stability in the upright position. Basically, IT2FLC uses a Type-2 Fuzzy Set (T2FS) and its membership function (MFs) composed of the lower MFs, upper MFs, and footprint of uncertainty (FOU). This is the reason that IT2FLC possessing the ability to handle cases of nonlinearities and uncertainties that occur in the system. Therefore, any disturbances that give at the back of the seat can be eliminated using the proposed controller, IT2FLC. Additionally, SDA implemented within the control strategy to acquire optimal values of the IT2FLC input-output control gains and parameters of its MFs further accommodated extensive fluctuations of the two-wheeled system; thus, ensuring a safe and comfortable experience among users via shorter traveled distance and lower magnitude of torques following disruptions. The two-wheeled wheelchair is designed using SimWise 4D software to subduing shortcomings of a linearized mathematical model where lengthy equation with various assumptions is required to represent the proposed system; without forgoing its nonlinearity and complexity. Moreover, a 70kg payload was also included to embody an average user, in simulating vertical extensions of the system from 0.11m to 0.25m. The completed model is then integrated with Matlab/Simulink for control design and performance evaluation through visualized simulations. The research has been compared to the previous controllers, Fuzzy Logic Control Type-1 (FLCT1), in gauging improvements and performance superiority. The significance of SDA-IT2FLC as the stability controller within the investigated system has been confirmed through current findings, which outperformed that of its predecessors (IT2FLC and FLCT1). Such results are supported through a significant reduction in traveled distance, tilt, and control torques, following a recorded 5.6% and 33.3% improvements on the stability of the system, to the performance of heuristically-tuned IT2FLC; as well as a 60% and 94% improvements in angular positions on the system, as compared to the FLCT1. Moreover, a 95.4% reduction in torques has been recorded for SDA-IT2FLC, as compared to that of FLCT1. Ultimately, SDAIT2FLC has demonstrated promising outcomes over its predecessors on maintaining the system’s stability in an upright position in terms of faster convergence and a significant reduction in traveled distance, tilt and control torques, proving itself as the robust controller for a double-link two-wheeled wheelchair with movable payload system.